SEKOLAH NASIONAL PLUS: PENTINGNYA MANUVER KEBIJAKAN - Elsina Sihombing (JURNAL PIONIR, 2020)
One of the major themes in educational effective research is about the maneuver of policy making which has a power of influencing the system of work at an organization especially at school. This article concerning about school policy and decision making on an International Standardized School (ISS)  in Indonesia of which the school is a kind of national plus / go international school, the policy that dealing with the school capacity building improvement in the particular country. Using coherent program dimension of capacity building framework, a qualitative study was conducted in Yadika Senior High School that located in a small city in Lubuklinggau South Sumatera, Indonesia. It is found that the interpretation to the ISS policy was changing, which established international standard classrooms is the salient aspect of the implementation of the policy. It is discovered that become an ISSS school has positive consequence regarding acknowledgment and its quality by the central government, besides, the school can gather additional fund from the Deputy of Institution as the owner of the private school, and donation  from parents as well to fufill all things that are needed. Document analysis revealed the school difficulties to overcome such as ‘international requirements’ to gain by all stakeholders of the school.  Keywords : Indonesia schools improvemen, national plus school